Reconceptualizing supply chain flows (SCFLOWS) - Ashraf, Muhammad Hasan; Yalcin, Mehmet G.; Hos, Rabia (The International Journal of Logistics Management, 2024)
Despite being a fundamental concept, the field of supply chain management (SCM) exhibits a significant lack of consensus regarding the definition of supply chain flows (SCFLOWS). Additionally, there has been an over-reliance on three flows – material, information and finance – while various other flows crucial to SCM performance have been overlooked. Hence, the purpose of this study is twofold: (1) to explore the multi-dimensional nature of SCFLOWS and (2) to identify additional flows beyond the commonly acknowledged ones that are vital for SCM performance.,This study employs various qualitative methods as part of the abduction process. The methods include in-depth interviews with logistics professionals, a Delphi study involving SCM scholars and a focus group comprising airline industry practitioners.,Seven SCFLOWS dimensions are identified and presented as SCFLOWS framework. Also, two additional flows, i.e. human and capital equipment, are proposed as vital to SCM performance.,This is the first study to introduce SCFLOWS framework to achieve consensus in the field. By introducing two additional flows, it proposes extending the SCFLOWS boundary to include various flows overlooked previously but pertinent to SCM performance. The SCFLOWS framework serves as a systematic guide to validate additional flows and represents an important step towards building SCM theory.
Keywords: dept.grad; peer-reviewed

Investigating the (Mis)alignment between Expenditures and Policy to Improve Multilingual Learner Programs - Correia, Amy; Hos, Rabia; Cahan, James (Journal of Educational Leadership and Policy Studies, 2024)
States and districts share an obligation to provide Multilingual Learners (MLLs) with access to high quality language programs that are proven to be effective in minimizing opportunity gaps between MLLs and non-MLLs. This article reviews how local education agencies (LEAs) allocated their state-issued funding to improve MLL language programs and increase student outcomes. Findings reveal that of the total state-issued MLL funding, LEAs used 88.7% on teacher salaries and benefits, 5.1% on teacher professional development, 4.9% on language program implementation, 0% on language program evaluation, and a small percentage of funding remained unspecified. Collectively, these findings indicate that LEAs did not adhere to the state's funding policies, nor did the state follow their own policies to regulate the LEAs' expenditures. We close with a discussion on how the state can improve their function as an organizational leader and serve as a model for other stakeholders in the shared obligation of the education of MLLs.
Keywords: Elementary Secondary Education; English (Second Language); English Language Learners; Expenditures; Financial Support; Fringe Benefits; Multilingualism; Outcomes of Education; Policy Analysis; Program Implementation; Program Improvement; Resource Allocation; School Districts; Second Language Learning; Second Language Programs; State Policy; Teacher Salaries; dept.grad